"Il mio problema è far fare le prefazioni dei russi": «Il mio problema è far fare le prefazioni dei russi» Italo Calvino and the Russian Literature in Cento-pagine (ENTHYMEMA, 2025)
The direction of Centopagine proved to be one of the most significant publishing activities undertaken by Italo Calvino, in terms of the responsibility undertaken, the work put in and the duration of the enterprise. Started in 1971 with the aim of collecting short novels from the past, and ended with Calvino's death in 1985, for Centopagine the presence of works of 19th-century Russian literature was essential. The books of some of the greatest Russian authors of the time – Chekhov, Dostoyevsky, Gogol’, Leskov, Pushkin and Tolstoy – appeared in the collection, and were in fact considered emblematic by Calvino to show, through concrete narrative examples, the mechanization and essence of the romanzesco, whose «rehabilitation» was at the centre of the literary recovery undertaken by Centopagine
Keywords: Italo Calvino; Centopagine; Publishing; Russian Literature; Peritexts